Pengaruh Kinerja Non-Financial Dan Kinerja Financial Terhadap Return Saham Dengan Risiko Sistematis Sebagai Variabel Moderasi - IZZAH, NUR; Wijaya Z, Rico; Friyani, Rita (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This research aims to examine the influence of non-financial performance and financial performance on stock returns with systematic risk as a moderating variable. The population in this study includes 86 mining companies listed on the Indonesia Stock Exchange, with a sample of 31 companies selected randomly and having published financial reports over a 5 year period. The research method used is quantitative, with secondary data obtained from sources such as idx.com, yahoo.finance.com, as well as the company's official website. The technique used to manage data in this study is data analysis technique through excel computer program and WarpPLS 7.0 software assistance. The research results reveal that the variables profitability, solvency, institutional ownership, independent commissioners, and board of commissioners meetings have a significant influence on stock returns. Meanwhile, the variables liquidity, operational cash flow, and audit committee do not show a significant influence on stock returns. Systematic risk as a moderating variable is able to strengthen the relationship between profitability, solvency, liquidity, audit committee and independent commissioners and stock returns. However, systematic risk is unable to strengthen the relationship between independent variables, namely operational cash flow, institutional ownership, and board of commissioners meetings, on stock returns. These findings demonstrate the selective role of systematic risk in moderating the relationship between various performance factors and stock returns.